2011
DOI: 10.4103/0301-4738.77043
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal neovascularization associated with coloboma of the choroid: A series of three cases

Abstract: Choroidal neovascularization (CNV) is a rare complication associated with coloboma of the choroid. We describe three cases of coloboma choroid where there was loss of vision due to CNV development at the edge of the coloboma. One was managed by photodynamic therapy alone and two were managed by a combination of reduced fluence PDT and intravitreal bevacizumab. Significantly we noted that one treatment session was sufficient to achieve regression of the CNV and improvement in visual acuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
(7 reference statements)
1
16
1
Order By: Relevance
“…Virtually, all previously published studies report bilateral disease between 70 and 80% in congenital glaucoma patients. [1459] Congenital glaucoma in this study is, however, observed in 92.3% of the patients. The frequency of unilateral disease in secondary congenital glaucoma was higher than in primary congenital glaucoma, probably owing to the more frequent observation of unilaterality in phakomatoses, and Peters anomaly.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Virtually, all previously published studies report bilateral disease between 70 and 80% in congenital glaucoma patients. [1459] Congenital glaucoma in this study is, however, observed in 92.3% of the patients. The frequency of unilateral disease in secondary congenital glaucoma was higher than in primary congenital glaucoma, probably owing to the more frequent observation of unilaterality in phakomatoses, and Peters anomaly.…”
Section: Discussioncontrasting
confidence: 58%
“…[1] In the former classification method, congenital glaucoma is classified into primary or secondary congenital glaucoma. Primary congenital glaucoma, also known as isolated trabeculodysgenesis, is typically an isolated idiopathic developmental abnormality of the trabecular meshwork in the absence of other ocular and systemic conditions.…”
mentioning
confidence: 99%
“…An interaction of these genes may explain the coexistence of the FEVR with coloboma. CNV is a known rare complication associated with choroidal coloboma 5. This case highlights the occurrence of these two anomalies in a single patient which, to the best of our knowledge, has not been reported before.…”
Section: Descriptionmentioning
confidence: 51%
“…[1][2][3][4] Choroidal neovascularization is a welldocumented complication of RCC in adults and children. 1,[8][9][10][11] Among the 9 cases reported in the literature (Table 2), the youngest child was a 19-month-old boy by Goodwin et al 8 Eight of these 9 patients reported progressive decrease of vision or metamorphopsia for at least 2 weeks. A history of retinal detachment was noted in 1 patient, the 5-year-old reported by Naithani et al 1 None of the patients had a history of prophylactic barrage laser.…”
Section: Discussionmentioning
confidence: 99%
“…Management options of coloboma-related CNVM are photocoagulation therapy, 8 photodynamic therapy (PDT) alone, 9,10 and antivascular endothelial growth factor (anti-VEGF) monotherapy 1 and in combination. 8 Here, we report 3 cases that were successfully treated with intravitreal bevacizumab (IVB) monotherapy, addressing the treatment protocol, outcome, and recurrence in eyes with CNVM associated with RCC.…”
mentioning
confidence: 99%